Potentially Inappropriate Medication (PIMs) Identification Using 2019 Beers Criteria at a Secondary Referral Hospital in Jakarta - Nurhasnah Nurhasnah; Daniek Viviandhari; Riska Nur Sakinah; Desi Wulandari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2022)
Drug information about Potentially Inappropriate Medications (PIMs) for elderly inpatients based on Beers 2019 is still limited in Indonesia. This study aimed to identify the incidence of PIMs using the 2019 Beers criteria in elderly patients and determine the factors associated with the incidence of PIMs. This research was observational with a cross-sectional approach. Data collection was carried out in the medical records section of a secondary referral hospital in Jakarta during August and September 2019. The number of samples was calculated using a sample size calculator, and data were obtained from the medical records of inpatients for the period January 2018-December 2018. The sampling of medical records was conducted with a non-probability sample with a purposive sampling technique. Inclusion criteria were medical records of inpatients aged 60 years or older. The exclusion criteria were patient medical records with incomplete data. The Beers 2019 criteria were used to identify PIMs. The results showed that from 325 medical records analyzed, PIMs were found in 122 (37.5%) elderly patients with a total incidence of 181 PIMs. Furosemide (25.4%) was the most common PIMs, followed by spironolactone (18.2%) and ranitidine (16%). The use of 10 medicines or more p<0.001, OR 4.26 95%CI (2.4-7.5) and a length of stay more than five days p=0.043 OR 1.65 95%CI (1.0- 2,6) was associated with a higher incidence of PIMs. However, age, gender, and the number of diagnoses were not significantly related to the incidence of PIMs. Health workers are advised to check serum creatinine in all hospitalized elderly patients and minimize the number of drugs used.